Acute biliary disease and acute pancreatitis - Delgado, Bolívar; Trostchansky, José (Cirugía del Uruguay, 1975)
Two distinct cases of acute biliopancreatic conditions are described from both conceptual and thera, peutic points of view. On one hand, acute obstructive cholecystitis with pancreatic reaction, which is mainly a gall bladder disease, although at the same time there may be pathology of the common bile duct, but not actually symptomatic. The pancreatic reaction is not significant and is expressed at laparotomy by edema of the hepatoduodenal ligament and the pancreas. The treatment is the usual one for acute obstructive cholecystitis. On the other hand, in cholecysto-pancreatitis and biliopancreatic peritonitis, there is a severe compromise of the two systems, biliary and pancreatic, produced by disease in the common bile duct, usually lithiasic, with common biliopancreatic channel and reflux. In cholecystopancreatitis the gal! bladder lesion is obvious, not obstructive, and demands surgery. In biliopancreatic peritonitis is biliary peritonitis, usually caused by permeation that demands surgery. In both cases external drainage of the common bile duct is necessary. Under these circumstances, a more aggressive approach is recommended with a view to erradicate by surgery, the biliary disease and its consequences. The latter cases are not usual, but acute cholecystitis is very frequent and emphasis is placed on the fact that its best prophylaxis is early and correct treatment of biliary lithiasis.